2019
DOI: 10.3389/fmicb.2019.02879
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Nuclear Antigen 1 Recruits Cyclophilin A to Facilitate the Replication of Viral DNA Genome

Abstract: Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA1)-mediated DNA episomal genome replication and persistence are essential for the viral pathogenesis. Cyclophilin A (CYPA) is upregulated in EBV-associated nasopharyngeal carcinoma (NPC) with unknown roles. In the present approach, cytosolic CYPA was found to be bound with EBNA1 into the nucleus. The amino acid 376-459 of the EBNA1 domain was important for the binding. CYPA depletion attenuated and ectopic CYPA expression improved EBNA1 expression in EBV-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…USP7 has been related to many diseases, such as lung cancer, cervical cancer, herpes simplex virus, and nasopharyngeal carcinoma by Epstein-Bar virus (EBV) [114][115][116][117]. USP7 plays an important role in tumorigenesis and progression by deubiquitinating a variety of tumor regulatory molecules [95] and is a promising target for the development of lead compounds.…”
Section: Usp7 a Conformational Rearrangement Of The Catalytic Triadmentioning
confidence: 99%
“…USP7 has been related to many diseases, such as lung cancer, cervical cancer, herpes simplex virus, and nasopharyngeal carcinoma by Epstein-Bar virus (EBV) [114][115][116][117]. USP7 plays an important role in tumorigenesis and progression by deubiquitinating a variety of tumor regulatory molecules [95] and is a promising target for the development of lead compounds.…”
Section: Usp7 a Conformational Rearrangement Of The Catalytic Triadmentioning
confidence: 99%
“…Soil texture was the most important attribute underpinning changes in soil bacterial taxonomic diversity and composition. Soil texture shapes the microhabitats for bacteria and other members of the soil microbial community [80]. Seaton et al [81] found that clay and silt particles were more important for soil bacterial composition than sand in a range of habitats including arable, improved, and unimproved grassland, broadleaved and coniferous woodland, and heathland.…”
Section: Changes In Bacterial Taxonomic Composition With Land Use and Depthmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) can exist in most people in a latent state, inseparable from its ability to escape and destroy the innate immune system ( Xin et al, 2019 ; Dang et al, 2021 ). EBV oncoprotein LMP1 promotes the expression of IRF7, which has been implicated in IFNs signaling in previous studies ( Ning et al, 2005 ).…”
Section: Cellular Dubs Exploited By Viruses To Support Self-replication and Immune Evasionmentioning
confidence: 99%